Succession Planning and the Sustainability of Transport Enterprises: A Study of Transport Business in Njombe and Iringa Regions - Tonya, Emmanuel Mgaya (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2018)
The main objective of this study was to explore succession planning and the sustainability of transport enterprises. The study was done in Njombe and Iringa regions. The study population was 240 individuals or family transporters; the sample size was 70 respondents. Stratified sampling techniques were used and a proportional distribution was done to select the respondents from the Njombe, Mufindi and Iringa urban. From the proportional distribution 18 respondents, 6 respondents and 46 respondents were picked from Njombe, Mufindi and Iringa districts respectively. The study based on trait and behavioural theories of leadership management. Qualitative content analysis was used for logical determining the relationship between strategic succession planning and business sustainability. Findings from this study revealed the casual factors influencing the higher failure rate of transport business and its sustainability includes lack of strategic succession planning particularly in the case of the first generation retirement from transport business. The study, observed that owners of business do not prepare successors in advance, this poses problems to business sustainability in Tanzania. The main contribution of knowledge is the issue of strategic succession planning as a factor to enhanced business sustainability, transport included.Â The study has recognized that, transport business is used as a venture for capital formation to other economic activities like housing, estate and hospitality. However, a guideline for systematic succession planning has been proposed to be used by transporters for sustainability.